Child Health Clinical Outcome Review Programme: The Mental Healthcare of Young People and Young Adults - Wood, Sophie; Rees, Sarah; Wang, Ting; Marchant, Amanda; Akbari, Ashley; John, Ann (International Journal of Population Data Science, 2018)
Introduction The diagnosis, management and services available for mental disorders are of growing concern and controversy in the UK. Transitional care between child and adult services and the interface between primary and secondary/ specialist services is often disjointed and thresholds for referral to Child and Adolescent Mental Health Services are high. Objectives and Approach Routinely collected healthcare datasets and data linkage were used to identify patterns of healthcare utilisation by young people and young adults with mental health disorders across the four UK Nations. We explored the extent to which routinely collected datasets can contribute to an assessment of the health needs and the quality of care that children and young people with mental health disorders receive. Data was requested from the national data providers in each country. A series of descriptive analyses were performed and methods were developed for cross- national comparisons to be made (e.g. Four Nation Person Spell). Results It is feasible to explore healthcare utilisation across the four countries of the UK using routine data. However the recording, availability and access varied considerably between countries, making meaningful comparisons challenging. Descriptive analyses showed strong deprivation gradients in the diagnoses and care provided for young people and young adults with mental health disorders. Depression and anxiety were the most commonly recorded mental health conditions in primary care. In secondary care drug/alcohol disorders and self-harm were the most commonly recorded. Re-admissions to emergency departments were higher for those admitted for self-harm or psychiatric conditions. Conclusion/Implications Routine data has the potential to make a difference to care. However collection and access needs to be standardised in order to improve efficiency and effectiveness in improving the care for children and young people with mental health disorders. MQ has funded an Adolescent Data Platform to facilitate this.